Instant messaging: The next best knowledge sharing tools in a workplace after e-mail? - Hanif Suhairi, Abu Bakar; Nor Azmi, Johari (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org